MDSCs mediate angiogenesis and predispose canine mammary tumor cells for metastasis via IL-28/IL-28RA (IFN-λ) signaling. - Joanna Mucha (Public Library of Science (PLoS), 2014)
Background Myeloid-derived suppressor cells (MDSCs) function in immunosuppression and tumor development by induction of angiogenesis in a STAT3-dependent manner. Knowledge of MDSC biology is mainly limited to mice studies, and more clinical investigations using spontaneous tumor models are required. Here we performed in vitro experiments and clinical data analysis obtained from canine patients. Methods Using microarrays we examined changes in gene expression in canine mammary cancer cells due to their co-culture with MDSCs. Further, using Real-time rt-PCR, Western blot, IHC, siRNA, angiogenesis assay and migration/invasion tests we examined a role of the most important signaling pathway. Results In dogs with mammary cancer, the number of circulating MDSCs increases with tumor clinical stage. Microarray analysis revealed that MDSCs had significantly altered molecular pathways in tumor cells in vitro. Particularly important was the detected increased activation of IL-28/IL-28RA (IFN-λ) signaling. The highest expression of IL-28 was observed in stage III/IV mammary tumor-bearing dogs. IL-28 secreted by MDSCs stimulates STAT3 in tumor cells, which results in increased expression of angiogenic factors and subsequent induction of angiogenesis by endothelial cells, epithelial-mesenchymal transition (EMT) and increased migration of tumor cells in vitro. Knockdown of IL-28RA decreased angiogenesis, tumor cell invasion and migration. Conclusions We showed for the first time that MDSCs secrete IL-28 (IFN-λ), which promotes angiogenesis, EMT, invasion and migration of tumor cells. Thus, IL-28 may constitute an interesting target for further therapies. Moreover, the similarity in circulating MDSC levels at various tumor clinical stages between canine and human patients indicates canines as a good model for clinical trials of drugs targeting MDSCs.